Towards Accountability and Improvement: Assessing the Efficacy of Faculty Evaluation Systems - Abhijit R. Abhang; Yash P. Gaike (International Journal of Electrical and Communication Engineering Technology, 2024)
This research suggests an online application system for examining teacher feedback in educational settings. To evaluate faculty performance based on a set of criteria and offer the required academic intervention programmes rooted in the creation of an all-encompassing faculty development programme, the suggested system gathers all the pertinent information from the feedback, which is now an essential component of the educational system. Compared to the current feedback evaluation method, which asks students to rate teachers according to predetermined criteria, the suggested Faculty Evaluation method (FES) is more adaptable and flexible. FES evaluates instructors' strengths and shortcomings in all areas that matter to pupils. Students, instructors, and the staff in charge of administering and processing the evaluation system will all gain from the study's outcome. Through the anonymous use of an online platform called FES, students can evaluate their professors' performance using a predetermined set of evaluation criteria and questions. Higher-ups at the institute may also utilise this information to assemble faculty groups that are suitable for certain teaching and administrative responsibilities. With the help of a mobile device, the assessor conducts a paperless evaluation of the teacher under the proposed Online Faculty Monitoring and Evaluation System. Because the software evaluation results satisfied the researcher's goals, they should be developed further. The generated study was very helpful and may be a great help to the institution, according to the general means of the system evaluation. The faculty members' improved usage was a result of their evaluations.
Keywords: Performance; Web-based application; administrate activities; software evaluation